2018
DOI: 10.1016/j.jstrokecerebrovasdis.2017.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs as Biomarkers for Acute Ischemic Stroke: A Systematic Review

Abstract: markers. This review aimed to systematically assess case-control studies investigating the 28 association of circulating microRNAs with acute ischemic stroke. Medline, CINAHL, Cochrane 29Library, Web of Science Scopus, and PubMed were searched for studies that examined the 30 association of circulating microRNAs in acute ischemic stroke patients. Studies meeting specific 31 inclusion and exclusion criteria (such as blood sample were obtained within 24 hours of an acute 32 ischemic stroke) were selected for dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 19 publications
1
49
0
1
Order By: Relevance
“…These discoveries have initiated the novel strategy of using peripheral blood miRNAs for non-invasive disease diagnosis (4). Research reported that peripheral blood miRNAs with specific expression changes can be found in multiple diseases, including tumor, diabetes, myocardial infarction, Parkinson' disease and Alzheimer's disease (11). In the present study, overexpression of miR-323 was found to significantly increase LDH activity level and inhibit cell viability in an in vitro model of ACI.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These discoveries have initiated the novel strategy of using peripheral blood miRNAs for non-invasive disease diagnosis (4). Research reported that peripheral blood miRNAs with specific expression changes can be found in multiple diseases, including tumor, diabetes, myocardial infarction, Parkinson' disease and Alzheimer's disease (11). In the present study, overexpression of miR-323 was found to significantly increase LDH activity level and inhibit cell viability in an in vitro model of ACI.…”
Section: Discussionsupporting
confidence: 55%
“…Certain miRNAs serve important roles in neurogenesis and neuronal function, even at low concentrations. The majority of miRNAs are located in the tissues and cells (11), while they can also stably exist in body fluids, including blood, urine and amniotic fluid (12). Human tissue miRNA detection can hardly be achieved or repeatedly used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, many studies have demonstrated that miRNAs are associated with the occurrence and development of various diseases (Lu et al, 2005;Liu et al, 2010;Li and He 2012;Di Gregoli et al, 2017). Some recent studies have demonstrated that the expression patterns of miRNAs are altered in patients with various neurological disorders, including ischemic stroke (Tan et al, 2009;Dewdney et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing attention has been given to secreting miRNAs. Circulating miRNAs have been reported as novel diagnostic or therapeutic targets in several human diseases, based on the analysis of miRNAs isolated from the plasma of patients [20,21,22]. However, the use of plasma miRNAs faces technical limitations because of the extremely low concentrations of miRNAs freely circulating in the plasma, leaving the underlying molecular mechanisms regulated by miRNAs poorly understood.…”
Section: Introductionmentioning
confidence: 99%